2011
DOI: 10.1039/c0mt00069h
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of rare earth elements in human bone within the lifespan

Abstract: For the first time, the contents of rare earth elements (REEs) in a rib bone of a healthy human were determined. The mean value of the contents of Ce, Dy, Er, Gd, La, Nd, Pr, Sm, Tb, and Yb (10 elements out of 17 total REEs), as well as the upper limit of means for Ho, Lu, Tm, and Y (4 elements) were measured in the rib bone tissue of 38 females and 42 males (15 to 55 years old) using inductively coupled plasma mass spectrometry (ICP-MS). We found age-related accumulation of REEs in the bone tissue of healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(53 citation statements)
references
References 34 publications
0
52
0
1
Order By: Relevance
“…177 Lu-LCP shows significant accumulation in the tumor, as well as accumulation in the nanoparticle clearing organs, the liver and spleen, as it is too large to clear renally. In contrast, free 177 Lu is an ion that is plenty small to clear through the kidneys, but also selectively accumulates in the bones, as lanthanide elements are known to do [16]. Free 177 Lu also shows some kidney accumulation, which may occur during the quick renal clearance of the element (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…177 Lu-LCP shows significant accumulation in the tumor, as well as accumulation in the nanoparticle clearing organs, the liver and spleen, as it is too large to clear renally. In contrast, free 177 Lu is an ion that is plenty small to clear through the kidneys, but also selectively accumulates in the bones, as lanthanide elements are known to do [16]. Free 177 Lu also shows some kidney accumulation, which may occur during the quick renal clearance of the element (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…Zhu et al (2005) suggested that long-term ingestion of REE had an influence on activities of some digestive enzymes, bringing about malabsorption and indigestion, which might further lead to a low-protein effect among the villagers of South Jangxi Province, China. In addition, the lighter REE tend to deposit in the liver (Zhu et al, 2005), whereas the heavier REE, in turn, in a rib bone due to their affinity to Ca 2+ (Zaichick et al, 2011). Zhu et al (1996cited after Fedele et al (2008) found a correlation between the high REE contents and the low intelligence quotient (IQ) among children.…”
Section: Environmental and Health Concernsmentioning
confidence: 97%
“…This indicates an incorporation in the formed degradation products (most likely calcium phosphates) and to a much lesser extend a release to the environment than theoretically possible. This behavior was observed in other studies 36 and can be attributed to rare earth elements being known to be "Bone homing" elements in vivo by replacing calcium in the crystal lattice of newly formed bone [37][38][39] .…”
Section: Discussionmentioning
confidence: 52%